Anthropometric measures associated with sarcopenia in outpatients with liver cirrhosis - Santos, Lívia A.A. [UNESP]; Lima, Talles B. [UNESP]; Ietsugu, Marjorie do Val [UNESP]; Nunes, Hélio R. de Carvalho [UNESP]; Qi, Xingshun; Romeiro, Fernando G. [UNESP] (Wiley, 2019)
Aim: The present study aimed to identify variables associated with sarcopenia in cirrhotic outpatients using clinical data, anthropometric measures and lab tests. In a single centre prospective study, 261 cirrhotic outpatients were followed on average for 2 years. The diagnostic criteria of sarcopenia were applied according to the current guidelines, combining muscle strength and appendicular muscle mass index. Methods: Age, sex, liver disease aetiology and the Model of End-Stage Liver Disease score were included as independent variables, as well as mid-arm circumference (MAC), body mass index and triceps skinfold. Multiple logistic regression was applied including all independent variables (maximum model). Then, the analysis was performed only with the variables that were significant in the first analysis (parsimonious model). Once the variable most related to sarcopenia was determined by the two models, the area under the receiver operator characteristic curve was calculated. Mortality rates were described for patients with and without sarcopenia. Results: Sarcopenia was diagnosed in 14 subjects (5.36%), and the variable best associated with sarcopenia was MAC (P < 0.01). The 1-year mortality rate of 35.71% found among subjects with sarcopenia was not significantly higher (P = 0.07) than the 15.38% observed among those without this condition. Conclusions: Before examinations requiring ionising radiation, patients with cirrhosis can be submitted to simple screening tools to identify those who have a high risk of sarcopenia, thus promoting a cost-effective assessment.
Keywords: body composition; chronic disease management; nutrition screening; nutritional status